Spigelia elbakyanii, a new species from Oaxaca, Mexico - Islas-Hernández, C. Sofia; Alvarado-Cárdenas, Leonardo O. (Phytotaxa, 2020)
A new species of Spigelia (Loganiaceae) from Oaxaca, Mexico, is described here. This species is similar to S. humboldtiana and S. anthelmia, due to its size and white flowers, but the leaf texture, phyllotaxy below the inflorescence, and the style length are characters that allow to recognize it as a new species. With this addition, Mexico reaches a total of 23 species of the genus, of which more than 50% are endemic or microendemic. This places the country as the second area of high diversity after Brazil. A detailed description and illustration of the new species, a dichotomous key and a distribution map of Spigelia species in Oaxaca are included.